EFEKTIVITAS PROGRAM PENGEMBANGAN KARIR DALAM MENINGKATKAN RETENSI KARYAWAN - Hartono, Sri; Wahyudiyono, Wahyudiyono; Karyono, Karyono; Farida, Ida; Rosyid, Bahrur (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the effectiveness of career development in increasing employee retention. This study uses a descriptive qualitative approach. Data were collected through several techniques, including in-depth interviews, observation, and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results of this study indicate that career development programs are proven effective in increasing employee retention, particularly through improving competency, motivation, and clarity of career direction, thereby increasing their loyalty and commitment to the organization. Although this program is effective as a retention strategy, equitable access to training and consistency of implementation still need to be improved so that its benefits can be felt by all employees.